Nanometer flower-shaped FeOOH / NiFe-LDH composite material as well as preparation method and application thereof

By generating FeOOH in situ in NiFe-LDH material, the problems of complex preparation process and poor performance of NiFe-LDH material in the prior art are solved, catalytic activity and stability are improved, and efficient electrocatalytic OER performance is achieved.

CN119287432APending Publication Date: 2025-01-10SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411416907.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing NiFe-LDH materials have complex processes, high temperatures and long time during the preparation process, resulting in poor conductivity and poor stability, which limits their application in OER catalytic materials.

Method used

By introducing the metal hydroxyoxide FeOOH and NiFe-LDH, NH4F is used as a morphological control agent to generate FeOOH in situ in homogeneous reaction, adjusting the atomic and electronic structure of NiFe-LDH and optimizing the catalytic performance.

Benefits of technology

The catalytic activity and stability of NiFe-LDH material is improved, the adsorption capacity of oxygen-containing substances is enhanced, the electrochemical impedance is reduced, the electron migration rate is improved, and excellent electrochemical performance is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287432A_ABST
    Figure CN119287432A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nanomaterials, and discloses a nanoflower-shaped FeOOH / NiFe-LDH composite material as well as a preparation method and application of the nanoflower-shaped FeOOH / NiFe-LDH composite material. The preparation method comprises the following steps: taking urea as a pH regulator, uniformly dispersing the urea, soluble nickel salt and soluble ferric iron salt in water, then adding a morphology control agent NH4F, and uniformly mixing to obtain a mixed solution; the mixed solution is subjected to a homogeneous reaction under the stirring condition, and after the reaction is finished, the nanoflower-shaped FeOOH / NiFe-LDH composite material is obtained. The preparation method is low in reaction temperature, short in reaction time and simple, the prepared composite material is of a three-dimensional structure, low in impedance and large in specific surface area, and the multi-phase composite material is multiple in charge transfer paths, high in electron migration rate, high in stability and excellent in electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanomaterials, and in particular to a nano-flower-shaped FeOOH / NiFe-LDH composite material and a preparation method and application thereof. Background Art

[0002] Transition metal layered double hydroxides, or LDH for short, have become a hot topic in the research of electrocatalytic water splitting in recent years due to their unique layered structure and high catalytic activity as well as adjustable layer cations and interlayer anions.

[0003] Among them, NiFe-based materials Ni 1-x Fe x (OH)2(A n- ) x / n mH2O, referred to as NiFe-LDH, combines Ni and Fe together organically, optimizing the adsorption energy between the oxygen evolution reaction intermediates and active sites at the anode during the electrocatalytic water process, and exhibiting excellent oxygen evolution reaction catalytic activity. The oxygen evolution reaction is Oxygen Evolution Reaction, referred to as OER.

[0004] However, the existing technology for preparing NiFe-LDH materials has a relatively complex preparation process, high preparation temperature, long preparation time, and is time-consuming and labor-intensive. Moreover, the prepared NiFe-LDH is mostly hexagonal nanosheets with a two-dimensional structure, and has a small active specific surface area, resulting in poor conductivity and stability, which in turn limits the application of NiFe-LDH as an OER catalytic material. Summary of the invention

[0005] In order to improve the catalytic activity of NiFe-LDH so that it can achieve efficient and long-lasting electrocatalytic OER reaction, the present invention provides a nanoflower-shaped FeOOH / NiFe-LDH composite material and its preparation method and application. The present invention uses oxyhydroxide FeOOH as an active site, and by compounding FeOOH with NiFe-LDH material, the interface binding of FeOOH and NiFe-LDH effectively adjusts the atomic and electronic structure of NiFe-LDH, optimizes the binding energy of the intermediate, and thus improves the OER performance of the NiFe-LDH material.

[0006] The nano-flower-shaped FeOOH / NiFe-LDH composite material of the present invention and its preparation method and application are achieved by the following technical solutions:

[0007] The first object of the present invention is to provide a method for preparing a nano-flower-shaped FeOOH / NiFe-LDH composite material.

[0008] It should be noted that in order to improve the conductivity and active sites of NiFe-LDH materials, the present invention attempts to modify and dope NiFe-LDH materials by introducing metal oxyhydroxides, thereby improving the catalytic activity of NiFe-LDH. Since metal oxyhydroxides are unstable, difficult to prepare and have poor conductivity, it is difficult to achieve effective compounding of metal oxyhydroxides with LDH materials. To this end, the present invention proposes the preparation method of the present invention after experimental exploration to achieve effective compounding of metal oxyhydroxides with LDH materials, so that the adsorption capacity of oxygen-containing substances can be improved by using oxyhydroxides as active sites, thereby effectively improving the catalytic performance of the composite catalyst material. And the present invention is specifically implemented through the following steps:

[0009] Step 1, prepare the precursor solution of NiFe-LDH:

[0010] Urea is used as a pH regulator, and urea, a soluble nickel salt and a soluble trivalent iron salt are uniformly dispersed in water to obtain a precursor solution of NiFe-LDH.

[0011] It should be noted that in order to uniformly precipitate the nickel ions provided by the soluble nickel salt and the iron ions provided by the soluble trivalent iron salt, urea is used as a pH regulator, so that it is fully mixed with the soluble nickel salt and the soluble trivalent iron salt to form a precursor solution for preparing NiFe-LDH, so as to form NiFe-LDH with uniform components in the subsequent reaction process.

[0012] In order to make urea and soluble nickel salt and soluble ferric salt evenly dispersed in water, so that urea can fully contact with soluble nickel salt and soluble ferric salt, and then make the nickel ions provided by the soluble nickel salt and the iron ions provided by the ferric salt evenly dispersed in the alkaline environment provided by urea, which is conducive to the formation of NiFe-LDH by the nickel ions provided by the soluble nickel salt and the iron ions provided by the ferric salt in the subsequent reaction process.

[0013] In some preferred embodiments of the present invention, the molar ratio of urea to soluble nickel salt and soluble trivalent iron salt is 24-26:4:1, so as to ensure that the added raw materials can form NiFe-LDH with uniform composition in the subsequent reaction process.

[0014] The present invention does not limit the specific type of the soluble nickel salt used, as long as it can provide nickel ions. In some preferred embodiments of the present invention, the soluble nickel salt used can be selected from one or both of Ni(NO3)2·6H2O and NiCl2·6H2O.

[0015] The present invention does not limit the specific type of the soluble ferric salt used, as long as it can provide ferric ions. In some preferred embodiments of the present invention, the soluble ferric salt used can be selected from one or both of Fe(NO3)3·9H2O and FeCl3·6H2O.

[0016] In order to ensure that urea is in full contact with soluble nickel salt and soluble ferric salt, urea, soluble nickel salt and soluble ferric salt need to be fully dissolved in the solvent, so the solvent used needs to have good solubility for urea, soluble nickel salt and soluble ferric salt, so the present invention preferably uses water as solvent. And in order to further ensure that urea, soluble nickel salt and soluble ferric salt can be fully dissolved in water, in some preferred embodiments of the present invention, the ratio of the amount of water used to the amount of the soluble nickel salt is 35mL~45mL:2mmol.

[0017] Step 2, prepare a mixed solution:

[0018] NH4F is used as a morphology control agent, and is added into the precursor solution of NiFe-LDH and mixed to obtain a mixed solution.

[0019] It should be noted that the present invention uses NH4F as a morphology control agent and uniformly disperses it in the precursor solution of the NiFe-LDH obtained above, so that in the subsequent homogeneous reaction process, a part of the Fe in the obtained NiFe-LDH can be converted into FeOOH by NH4F, thereby achieving in-situ composite FeOOH on the surface of the NiFe-LDH material, thereby preparing to obtain a FeOOH / NiFe-LDH composite material.

[0020] The present invention found in the process of exploration that the amount of NH4F has an important influence on the conversion of Fe into FeOOH. When the molar ratio of NH4F to soluble trivalent iron salt is lower than 5:1, LDH nanosheets cannot be nucleated; and when the molar ratio of NH4F to soluble trivalent iron salt is higher than 9:1, FeOOH will be completely converted into LDH, and the performance will be reduced. In order to ensure that the added NH4F can convert part of the Fe in NiFe-LDH into FeOOH to achieve the above effect, in some preferred embodiments of the present invention, the molar ratio of NH4F to the soluble trivalent iron salt is 5 to 9:1.

[0021] In order to ensure that the added NH4F can be evenly dispersed in the precursor solution of NiFe-LDH obtained above, in some preferred embodiments of the present invention, after the addition of NH4F, stirring is performed for 20min to 40min to fully mix it. The present invention does not limit the specific stirring rate, as long as the solution forms a vortex flow.

[0022] Step 3, homogeneous reaction:

[0023] Under stirring conditions, the mixed solution is subjected to a homogeneous reaction at 110° C. to 130° C., and after the reaction is completed, the nano-flower-shaped FeOOH / NiFe-LDH composite material is obtained.

[0024] It should be noted that in order to ensure that the components in the mixed solution are fully contacted and reacted in the solvent environment, the present invention preferably performs a homogeneous reaction under stirring, so that during the stirring homogeneous reaction, the nickel ions provided by the soluble nickel salt and the iron ions provided by the soluble trivalent iron salt react with the alkaline environment generated by the thermal decomposition of urea to form NiFe-LDH. At the same time, the F ions in the morphology control agent NH4F affect the nucleation of iron ions to generate FeOOH in situ, thereby realizing in-situ composite FeOOH on the basis of the formed NiFe-LDH, greatly improving the binding force between FeOOH and LDH materials, so that FeOOH is stably present on the LDH material, and the effective composite of metal hydroxide oxide and LDH material is realized, thereby obtaining a nano-flower-like FeOOH / NiFe-LDH composite material.

[0025] In order to further ensure that the nanoflower-shaped FeOOH / NiFe-LDH composite material can be obtained by reflux reaction, in some preferred embodiments of the present invention, the homogeneous reaction time is 8h to 24h. In other preferred embodiments of the present invention, the stirring rate of the homogeneous reaction is 25r / min to 75r / min.

[0026] In some preferred embodiments of the present invention, the reaction temperature of the homogeneous reaction is 120°C.

[0027] It is understandable that, since the homogeneous reaction is carried out in a solvent environment, the target product nanoflower-shaped FeOOH / NiFe-LDH composite material is also present in the solvent environment. In order to facilitate the utilization of the target product, the reaction solution obtained by the homogeneous reaction needs to be post-processed, that is, the reaction solution needs to be firstly subjected to solid-liquid separation to obtain a precipitate, and then the solvent and other impurities remaining on the surface of the precipitate are removed by washing, and then dried to remove the detergent used for washing, so as to obtain a pure nanoflower-shaped FeOOH / NiFe-LDH composite material. Among them, in some preferred embodiments of the present invention, for ease of operation, solid-liquid separation is performed by filtering. In some preferred embodiments of the present invention, during washing, deionized water and anhydrous ethanol are used to alternately wash until it is close to neutral.

[0028] In some preferred embodiments of the present invention, the drying temperature is 55° C. to 65° C., and the drying time is 6 h to 16 h.

[0029] The second object of the present invention is to provide a nanoflower-shaped FeOOH / NiFe-LDH composite material prepared by the above preparation method.

[0030] The third object of the present invention is to provide an application of the above-mentioned nanoflower-shaped FeOOH / NiFe-LDH composite material in catalytic electrolysis of water for oxygen evolution.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The invention uses urea as a pH regulator, mixes the urea with a soluble nickel salt and a soluble trivalent iron salt in water to obtain a precursor solution of NiFe-LDH; uses NH4F as a morphology control agent, and evenly disperses the NH4F in the precursor solution of NiFe-LDH to obtain a mixed solution; and then performs hydrothermal treatment on the mixed solution, so that nickel ions provided by the soluble nickel salt, iron ions provided by the soluble trivalent iron salt react with an alkaline environment generated by thermal decomposition of urea to form NiFe-LDH. Meanwhile, F ions in the morphology control agent NH4F affect the nucleation of iron ions to in-situ generate FeOOH, thereby realizing in-situ composite FeOOH on the basis of the formed NiFe-LDH, and thereby obtaining a nano-flower-shaped FeOOH / NiFe-LDH composite material. The present invention realizes in-situ compounding of FeOOH during the reaction process of preparing NiFe-LDH material, thereby greatly improving the binding force between FeOOH and LDH material, making FeOOH stably present on LDH material, and realizing effective compounding of metal hydroxide FeOOH and LDH material. The generated FeOOH not only has certain electrocatalytic activity and high adsorption capacity for oxygen-containing substances, but also increases the charge transfer path of the overall material, thereby improving the electron migration rate, thereby effectively improving the catalytic performance of the composite catalyst material, so that the nano-flower-shaped FeOOH / NiFe-LDH composite material prepared by the present invention has excellent electrochemical performance.

[0033] The present invention realizes the composite material with a three-dimensional nanoflower structure by compounding FeOOH and LDH materials by adjusting the addition amount of NH4F, and adjusts the interface of FeOOH and LDH materials by NH4F to adjust the atomic and electronic structure of NiFe-LDH materials, optimize the binding energy of intermediates, and thus improve the OER performance. The test results show that when the composite material of the present invention is used for electrolysis of water for oxygen evolution, the required overpotential is less than 300mV, the electrochemical impedance is about 9.8Ω, and the internal resistance is small.

[0034] The preparation method of the present invention has low reaction temperature, short reaction time, simple method, and the prepared composite material has a three-dimensional structure, low impedance, large specific surface area, multi-phase composite material has multiple charge transfer paths, fast electron migration rate, strong stability, and excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The XRD spectra of NFL-5F of Example 1, NFL-7F of Example 2, and NFL-9F of Example 3 are shown.

[0036] Figure 2 This is the XRD spectrum of NiFe-LDH of Comparative Example 1.

[0037] Figure 3 This is a SEM image of NFL-5F of Example 1.

[0038] Figure 4 This is the SEM of NFL-7F of Example 2.

[0039] Figure 5 This is the SEM image of NFL-9F of Example 3.

[0040] Figure 6 These are the OER performance test results of NFL-5F of Example 1, NFL-7F of Example 2, NFL-9F of Example 3, and the commercial catalyst RuO2. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention will be described clearly and completely below.

[0042] Example 1

[0043] This embodiment provides a nanoflower-shaped FeOOH / NiFe-LDH composite material, and the preparation method thereof is as follows:

[0044] Step 1, prepare the precursor solution of NiFe-LDH:

[0045] 0.5 mmol of Fe(NO3)3·9H2O, 2 mmol of Ni(NO3)2·6H2O and 12.5 mmol of urea were placed in 40 mL of deionized water and mixed to obtain a precursor solution of NiFe-LDH.

[0046] Step 2, prepare a mixed solution:

[0047] 2.5 mmol of NH4F was added to the precursor solution of NiFe-LDH obtained in step 1 above, and stirred for 30 min to mix it well to obtain a uniformly dispersed mixed solution.

[0048] Step 3, homogeneous reaction:

[0049] 3.1) The mixed solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and kept in a homogeneous reactor at 120° C. and 50 r / min for 24 h to obtain a reaction solution.

[0050] 3.2) The reaction solution in 3.1) was cooled to room temperature and filtered to obtain a precipitate.

[0051] 3.3) The precipitate of 3.1) was washed alternately with deionized water and anhydrous ethanol until it was nearly neutral, and dried at 60° C. for 12 h. The obtained solid product was a nanoflower-like FeOOH / NiFe-LDH composite material with a yield of 9.64%.

[0052] The nanoflower-shaped FeOOH / NiFe-LDH composite material of this embodiment is recorded as NFL-5F.

[0053] Example 2

[0054] This embodiment provides a nanoflower-shaped FeOOH / NiFe-LDH composite material, and the preparation method thereof is as follows:

[0055] Step 1, prepare the precursor solution of NiFe-LDH:

[0056] 0.5 mmol of Fe(NO3)3·9H2O, 2 mmol of Ni(NO3)2·6H2O and 12.5 mmol of urea were placed in 40 mL of deionized water and mixed to obtain a precursor solution of NiFe-LDH.

[0057] Step 2, prepare a mixed solution:

[0058] 3.5 mmol of NH4F was added to the precursor solution of NiFe-LDH obtained in step 1 above, and stirred for 30 min to mix it well to obtain a uniformly dispersed mixed solution.

[0059] Step 3, homogeneous reaction:

[0060] 3.1) The mixed solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and kept in a homogeneous reactor at 120° C. and 50 r / min for 12 h to obtain a reaction solution.

[0061] 3.2) The reaction solution in 3.1) was cooled to room temperature and filtered to obtain a precipitate.

[0062] 3.3) The precipitate of 3.1) was washed alternately with deionized water and anhydrous ethanol until it was nearly neutral, and dried at 60° C. for 12 h. The obtained solid product was a nanoflower-like FeOOH / NiFe-LDH composite material with a yield of 13.34%.

[0063] The nanoflower-shaped FeOOH / NiFe-LDH composite material of this embodiment is recorded as NFL-7F.

[0064] Example 3

[0065] This embodiment provides a nanoflower-shaped FeOOH / NiFe-LDH composite material, and the preparation method thereof is as follows:

[0066] Step 1, prepare the precursor solution of NiFe-LDH:

[0067] 0.5 mmol of Fe(NO3)3·9H2O, 2 mmol of Ni(NO3)2·6H2O and 12.5 mmol of urea were placed in 40 mL of deionized water and mixed to obtain a precursor solution of NiFe-LDH.

[0068] Step 2, preparing a mixed solution:

[0069] Then, 4.5 mmol of NH4F was added to the precursor solution of NiFe-LDH obtained in step 1, and stirred for 30 min to mix well to obtain a uniformly dispersed mixed solution.

[0070] Step 3, homogeneous reaction:

[0071] 3.1) The mixed solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and kept in a homogeneous reactor at 120° C. and 50 r / min for 12 h to obtain a reaction solution.

[0072] 3.2) The reaction solution in 3.1) was cooled to room temperature and filtered to obtain a precipitate.

[0073] 3.3) The precipitate of 3.1) was washed alternately with deionized water and anhydrous ethanol until it was nearly neutral, and dried at 60° C. for 12 h. The obtained solid product was a nanoflower-like FeOOH / NiFe-LDH composite material with a yield of 14.36%.

[0074] The nanoflower-shaped FeOOH / NiFe-LDH composite material of this embodiment is recorded as NFL-9F.

[0075] Example 4

[0076] This embodiment provides a nanoflower-shaped FeOOH / NiFe-LDH composite material, and the preparation method thereof is as follows:

[0077] Step 1, prepare the precursor solution of NiFe-LDH:

[0078] 0.5 mmol of Fe(NO3)3·9H2O, 2 mmol of Ni(NO3)2·6H2O and 12 mmol of urea were placed in 40 mL of deionized water and mixed to obtain a precursor solution of NiFe-LDH.

[0079] Step 2, prepare a mixed solution:

[0080] 3.5 mmol of NH4F was added to the precursor solution of NiFe-LDH obtained in step 1 above, and stirred for 30 min to mix it well to obtain a uniformly dispersed mixed solution.

[0081] Step 3, homogeneous reaction:

[0082] 3.1) The mixed solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and kept in a homogeneous reactor at 110° C. and 25 r / min for 8 h to obtain a reaction solution.

[0083] 3.2) The reaction solution in 3.1) was cooled to room temperature and filtered to obtain a precipitate.

[0084] 3.3) The precipitate of 3.1) was washed alternately with deionized water and anhydrous ethanol until it was nearly neutral, and dried at 60° C. for 12 h. The obtained solid product was a nanoflower-like FeOOH / NiFe-LDH composite material.

[0085] Example 5

[0086] This embodiment provides a nanoflower-shaped FeOOH / NiFe-LDH composite material, and the preparation method thereof is as follows:

[0087] Step 1, prepare the precursor solution of NiFe-LDH:

[0088] 0.5 mmol of Fe(NO3)3·9H2O, 2 mmol of Ni(NO3)2·6H2O and 13.0 mmol of urea were placed in 40 mL of deionized water and mixed to obtain a precursor solution of NiFe-LDH.

[0089] Step 2, prepare a mixed solution:

[0090] 4.5 mmol of NH4F was added to the precursor solution of NiFe-LDH obtained in step 1 above, and stirred for 30 min to mix it well to obtain a uniformly dispersed mixed solution.

[0091] Step 3, homogeneous reaction:

[0092] 3.1) The mixed solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and kept in a homogeneous reactor at 130° C. and 75 r / min for 16 h to obtain a reaction solution.

[0093] 3.2) The reaction solution in 3.1) was cooled to room temperature and filtered to obtain a precipitate.

[0094] 3.3) The precipitate of 3.1) was washed alternately with deionized water and anhydrous ethanol until it was nearly neutral, and dried at 60° C. for 12 h. The obtained solid product was a nanoflower-like FeOOH / NiFe-LDH composite material.

[0095] Comparative Example 1

[0096] This comparative example provides a NiFe-LDH nanocatalyst, and its preparation method is as follows:

[0097] Step 1, prepare the precursor solution of NiFe-LDH:

[0098] 0.5 mmol of Fe(NO3)3·9H2O, 2 mmol of Ni(NO3)2·6H2O and 12.5 mmol of urea were placed in 40 mL of deionized water and mixed to obtain a precursor solution of NiFe-LDH.

[0099] Step 2, preparing a mixed solution:

[0100] Then, 12.5 mmol of NH4F was added to the precursor solution of NiFe-LDH obtained in the above step 1, and stirred for 30 minutes to mix it well to obtain a uniformly dispersed mixed solution.

[0101] Step 3, homogeneous reaction:

[0102] 3.1) The mixed solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and kept in a homogeneous reactor at 100° C. and 30 r / min for 24 h to obtain a reaction solution.

[0103] 3.2) The reaction solution in 3.1) was cooled to room temperature and filtered to obtain a precipitate.

[0104] 3.3) The precipitate of 3.1) was washed alternately with deionized water and anhydrous ethanol until it was nearly neutral, and dried at 60° C. for 24 h to obtain a powder material, i.e., a solid product, with a yield of 7.16%.

[0105] The NiFe-LDH nanocatalyst of this comparative example is recorded as NiFe-LDH.

[0106] That is, the difference between this comparative example and Example 1 is only that:

[0107] In this comparative example, an excess amount of NH4F was added.

[0108] Experimental Section

[0109] (I) XRD test

[0110] The present invention takes NFL-5F of Example 1, NFL-7F of Example 2 and NFL-9F of Example 3 as examples, and performs XRD tests on them respectively, and the test results are as follows: Figure 1 shown.

[0111] And by Figure 1 It can be seen that NiFe-LDH PDF#40-0215 ​​is the PDF standard card of NiFe-LDH, and FeOOH PDF#34-1266 is the PDF standard card of FeOOH.

[0112] By comparing NFL-5F, NFL-7F, NFL-9F and NiFe-LDH PDF#40-0215, it can be seen that the composite materials of Examples 1 to 3 all contain the characteristic peaks of NiFe-LDH, indicating that NiFe-LDH is successfully synthesized in the materials prepared in Examples 1 to 3 of the present invention.

[0113] By comparing NFL-5F, NFL-7F, NFL-9F and FeOOH PDF#34-1266, it can be seen that NFL-5F and NFL-7F both contain obvious characteristic peaks of FeOOH, proving that FeOOH is successfully formed in the materials prepared in Examples 1 and 2 of the present invention, indicating that the materials prepared in Examples 1 and 2 of the present invention are all composite materials of NiFe-LDH and FeOOH. However, almost no obvious characteristic peaks of FeOOH are observed in the NFL-9F sample, indicating that when the amount of ammonium fluoride added is increased to 9:1, most of FeOOH has been converted into NiFe-LDH, and the content of FeOOH is very small.

[0114] In order to further verify the effect of the addition amount of NH4F on the formation of FeOOH, the present invention also carried out XRD test on the NiFe-LDH of comparative example 1, and the test results are as follows: Figure 2 shown.

[0115] Figure 2 , NiFe-LDH is the XRD spectrum of Comparative Example 1, and NiFe-LDH PDF#40-0215 ​​is the PDF standard card of NiFe-LDH. By comparing the XRD spectrum of Comparative Example 1 and the PDF standard card of NiFe-LDH, it can be seen that when the molar ratio of NH4F to the soluble trivalent iron salt is 25:1, the material obtained at this time does not contain FeOOH and is pure phase NiFe-LDH.

[0116] Based on the above, in order to ensure that the material prepared in the present invention is a FeOOH / NiFe-LDH composite material, the present invention preferably limits the amount of NH4F added to a molar ratio of NH4F to soluble trivalent iron salt of 5 to 9:1, more preferably 5 to 7:1.

[0117] (ii) SEM test

[0118] The present invention takes NFL-5F of Example 1, NFL-7F of Example 2 and NFL-9F of Example 3 as examples, and performs SEM tests on them respectively, and the test results are as follows: Figure 3-Figure 5 shown.

[0119] in, Figure 3 : is the SEM image of NFL-5F of Example 1. It can be seen that NFL-5F of Example 1 has been initially formed into a 3D nanoflower-like structure, and the composed nanosheets are relatively thick and have a small particle size of about 1 μm.

[0120] Figure 4 : is the SEM image of NFL-7F of Example 2. It can be seen that NFL-7F of Example 2 is a 3D nanoflower-like material, the nanosheets it consists of are relatively thin and have a relatively large particle size of about 2 μm.

[0121] Figure 5 This is the SEM image of NFL-9F of Example 3. It can be seen that NFL-9F of Example 3 is a 3D nanoflower-like material, and the composed nanosheets are relatively thin and have a small particle size of about 500 nm.

[0122] And by comparison Figure 3-Figure 5 It can be seen that the composite materials of Examples 1 to 3 are all agglomerated nanoflower-like materials with large specific surface areas. Among them, NFL-7F has the largest particle size and less agglomeration, which indicates that the electrochemical active surface area is large and there are many active sites.

[0123] Based on the above results, it can be seen that the addition amount of NH4F can not only affect the formation of FeOOH, but also affect the morphology structure and size of the overall material. This verifies that the NH4F described in the previous part of the present invention, as a morphology controller, can affect the nucleation of iron ions to generate FeOOH in situ, thereby realizing in-situ composite FeOOH on the basis of the formed NiFe-LDH, greatly improving the binding force between FeOOH and LDH materials, making FeOOH stably present on LDH materials, realizing effective composite of metal hydroxide oxide and LDH materials, and the interfacial bonding of FeOOH and NiFe-LDH effectively regulates the atomic and electronic structure of NiFe-LDH, optimizes the binding energy of the intermediate, and obtains nanoflower-like FeOOH / NiFe-LDH composite materials.

[0124] (III) OER performance test

[0125] The present invention takes NFL-5F of Example 1, NFL-7F of Example 2 and NFL-9F of Example 3 as examples, and takes commercial catalyst RuO2 as a control example, and conducts OER performance tests respectively, and the test results are as follows: Figure 6 shown.

[0126] The test method is a standard three-electrode system, with mercury / mercury oxide electrode as the reference electrode, graphite as the counter electrode, and the prepared powder sample and nafion ground into ink-like modified glassy carbon electrode as the working electrode.

[0127] And by Figure 6 The test results show that NFL-7F can achieve 50 and 100 mA cm at low overpotentials of 270 mV and 297 mV. -2 The current density of the samples is the lowest compared to the other samples, with NFL-5F reaching 50 and 100 mA cm -2 The current density required for the NFL-9F is 50 and 100 mA cm -2 The current density required for the reaction is 281mV and 319mV respectively, which is better than the performance of the commercial catalyst RuO2. This shows that FeOOH has a certain electrocatalytic activity, and the generation of FeOOH increases the charge transfer path of the catalyst, thereby increasing the electron migration rate. It proves that the in-situ compounding of FeOOH in the reaction process of preparing NiFe-LDH material can significantly improve the intrinsic electrocatalytic oxygen evolution activity of NiFe-LDH.

[0128] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a nanoflower-shaped FeOOH / NiFe-LDH composite material, characterized in that: The following steps are involved: Urea is used as a pH regulator, and urea, a soluble nickel salt and a soluble trivalent iron salt are uniformly dispersed in water to obtain a precursor solution of NiFe-LDH; Using NH4F as a morphology control agent, uniformly dispersing it in the precursor solution of NiFe-LDH to obtain a mixed solution; Under stirring conditions, the mixed solution is subjected to a homogeneous reaction at 110° C. to 130° C., and after the reaction is completed, the nano-flower-shaped FeOOH / NiFe-LDH composite material is obtained.

2. The preparation method according to claim 1, characterized in that The molar ratio of the urea to the soluble nickel salt and the soluble trivalent iron salt is 24-26:4:

1.

3. The preparation method according to claim 1, characterized in that: The molar ratio of the NH4F to the soluble trivalent iron salt is 5 to 9:

1.

4. The preparation method according to claim 1, characterized in that: The soluble trivalent iron salt is one or two of Fe(NO3)3·9H2O and FeCl3·6H2O.

5. The preparation method according to claim 1, characterized in that: The soluble nickel salt is one or both of Ni(NO3)2·6H2O and NiCl2·6H2O.

6. The preparation method according to claim 1, characterized in that: The reaction temperature of the homogeneous reaction is 120°C.

7. The preparation method according to claim 1, characterized in that: The reaction time of the homogeneous reaction is 8h to 24h.

8. The preparation method according to claim 1, characterized in that: The usage ratio of the water to the soluble nickel salt is 35mL-45mL:2mmol.

9. A nanoflower-shaped FeOOH / NiFe-LDH composite material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the nanoflower-shaped FeOOH / NiFe-LDH composite material according to claim 9 in catalytic electrolysis of water for oxygen evolution.

Citation Information

Cited By

  • Nitrogen-hybridized honeycomb carbon loaded FeOOH / FeNiCo-LDH heterostructure nano composite material as well as preparation method and application of nitrogen-hybridized honeycomb carbon loaded FeOOH / FeNiCo-LDH heterostructure nano composite material

    CN119332285A

  • Aza-hybridized honeycomb carbon loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite, a preparation method and application thereof

    CN119332285B